Comparison between American and European legislation in the therapeutical and alimentary bacteriophage usage - Naureen, Zakira; Malacarne, Daniele; Anpilogov, Kyrylo; Dautaj, Astrit; Camilleri, Giorgio; Cecchin, Stefano; Bressan, Simone; Casadei, Arianna; Albion, Elena; Sorrentino, Elisa; Beccari, Tommaso; Dundar, Munis; et al. (Acta Biomedica Atenei Parmensis, 2020)
Bacteriophages, though discovered a century ago, still lag behind in the race of antimicrobials due to scarce information about their biology, pharmacology, safety and suitability as therapeutic agents. Although they possess several capabilities of practical utility in medicine, they are still unable to satisfy the regulatory standards set by the regulatory authorities in both United States (US) and European Union (EU). Bacteriophages and their products (lysins) are considered as drugs, therefore they should follow the same route of the chemical drugs in order to achieve regulatory approvals for commercial production and application. However, lack of definitive guidelines and regulations has rendered bacteriophages less attractive to pharmaceutical companies and funding agencies, making it difficult for clinicians and researchers to set up wide scale clinical trials in order to prove efficacy, safety and stability of bacteriophages and their products. In this review, we will discuss the current regulations for developing phages and phage-based products for therapeutic purposes in the US and EU.